Assertive Training Intervention on Anger Control in Patients with Violent Behavior with Paranoid Schizophrenia - Gunawan, Asep; Sulistiarini, Sulistiarini (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Paranoid schizophrenia is characterized by a cycle of relapses. This relapse is usually caused by bad events before they are revived with anger. Violent behavior is that and anger or rage. A problem that usually results from violent behavior is the patient's inability to control his anger. Anger management must be done to prevent unwanted things, one way to control violent behavior is through verbal interventions, namely assertiveness training. Based on WHO (2021). 35 million people have depression, 60 million have bipolar disorder, 47.5 million have dementia and 24 million have paranoid schizophrenia. Purpose: The purpose of this case study is to provide a nurse for patients with violent behavior with a self-efficacy training intervention for anger management. The method used is a descriptive and case study approach. The sampling technique was adopted by one patient with paranoid schizophrenia and violent behavior problems in BLUD Banjar City Hospital. Method: a nursing process-based method using a qualitative descriptive design that includes assessment, diagnosis, intervention, implementation, and evaluation. Nursing refers to SDKI, SIKI, SLKI, and nursing assessments are documented using the SOAPIER method. A researcher conducted a thought-stopping therapeutic intervention for patients suffering from auditory hallucinations. A random sampling technique was used in this case study, ie one patient with auditory hallucinations was included. The analysis method uses interviews, observations and documentation. Result: The results of this study in the evaluation phase showed that the patients often threw tantrums, hit the walls, kicked the doors, spoke rudely quickly and sharply. Prescribed nursing diagnosis is violent behavior refers to Indonesian Nursing Diagnosis Standards (SDKI), intervention refers to Indonesian Nursing Intervention Standards (SIKI), Indonesian Nursing Outcome Standards (SLKI), evaluation and documentation refers to SOAPIER. The intervention uses 3 strategies to implement violent behavior and the focus of the intervention is assertiveness training. Conclusion: Providing an anger management training program for patients with violent behavior has been shown to be effective in paranoid schizophrenic patients with violent behavior problems.